STUDENTS’ ANXIETY IN ENGLISH SPEAKING AMONG GRADE XI STUDENTS AT SMAN 3 PEMATANGSIANTAR - Helen Renata Br Simanungkalit; Dumaris E. Silalahi; Novra Melisa P. Hutabarat (RADJA PUBLIKA, 2025)
Speaking anxiety is one of the major affective barriers that hinder students’ oral performance in English as a Foreign Language (EFL) classrooms. This study aims to investigate the levels, forms, and contributing factors of speaking anxiety among Grade XI students at SMAN 3 Pematangsiantar. Using a qualitative approach with a phenomenological design, data were collected through questionnaires, interviews, and classroom observations. The findings reveal that students experience a high level of speaking anxiety influenced by five interrelated factors: psychological, linguistic, pedagogical, sociocultural, and environmental. Psychological factors such as fear of making mistakes, low self-confidence, and fear of negative evaluation emerged as the most dominant contributors. Linguistic limitations, particularly vocabulary shortages, pronunciation difficulties, and grammatical concerns, also increased students’ hesitation to speak. Pedagogical aspects, including teacher correction styles, unclear task instructions, and difficult speaking tasks, further intensified anxiety. Sociocultural influences, such as peer judgment and cultural norms of silence, shaped students’ reluctance to speak, while environmental conditions like large class sizes and limited speaking opportunities outside the classroom exacerbated the problem. The study concludes that speaking anxiety is a complex and multidimensional issue requiring comprehensive support from teachers and institutions. Creating a more supportive, communicative, and low-anxiety classroom environment is essential for improving students’ speaking confidence and fluency.